2009
DOI: 10.1369/jhc.2009.953471
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Phosphodiesterase 2A in Multiple Mammalian Species

Abstract: Phosphodiesterases (PDEs) comprise a family of enzymes that regulate the levels of cyclic nucleotides, key second messengers that mediate a diverse array of functions. PDE2A is an evolutionarily conserved cGMP-stimulated cAMP and cGMP PDE. In the present study, the regional and cellular distribution of PDE2A in tissues of rats, mice, cynomolgus monkeys, dogs, and humans was evaluated by immunohistochemistry. A polyclonal antibody directed to the C-terminal portion of PDE2A specifically detected PDE2A by Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 37 publications
6
123
0
Order By: Relevance
“…Western blot analysis of human brain extracts with anti-PDE2A antibodies revealed that PDE2A immunoreactivity was prominently observed in the striatum, cingulate cortex, prefrontal cortex, and hippocampus, with no detectable signal in the cerebellum (4). A blocking study in humans would be needed to validate the suitability of the cerebellum as a reference region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis of human brain extracts with anti-PDE2A antibodies revealed that PDE2A immunoreactivity was prominently observed in the striatum, cingulate cortex, prefrontal cortex, and hippocampus, with no detectable signal in the cerebellum (4). A blocking study in humans would be needed to validate the suitability of the cerebellum as a reference region.…”
Section: Discussionmentioning
confidence: 99%
“…In non-central nervous system tissues, PDE2A is highly expressed in adrenal glands and vascular endothelial cells in which it may regulate vascular permeability (4). The development of a PDE2A radioligand would allow the evaluation of disease-specific changes (e.g., in schizophrenia) and potential inhibitor drugs.…”
mentioning
confidence: 99%
“…In vitro autoradiographic studies were accomplished by incubating sagittal sections of rat brain with [ , which is consistent with the distribution pattern of PDE2A protein in rat brain [9,11]. Therefore, we assume that the novel radioligands might be appropriate for in vitro imaging of PDE2A.…”
Section: In Vitro Autoradiographic Studies In Rat Brainmentioning
confidence: 78%
“…The PDE2A protein is highly and specifically expressed in particular brain regions such as striatum, cortex, hippocampus, substantia nigra, amygdala, and in olfactory neurons [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme thus contributes to the crosstalk between these two second messenger pathways (Zaccolo & Movsesian 2007). PDE2A is strongly expressed in the brain with a moderate presence in peripheral tissues such as the adrenal gland and heart and skeletal muscle (Rosman et al 1997, Sadhu et al 1999, Stephenson et al 2009. In addition, PDE2A expression has been observed in rat (Velardez et al 2000, Stephenson et al 2009) and human pituitary (Lennox et al 2011).…”
Section: Pde2a3 Three Isoforms Of Pde2a (Pde2a1 Pde2a2mentioning
confidence: 99%